Инженер- геологийн судалгаа, шинжилгээний өнөөгийн байдал, цаашдын зорилго - Т.Бээжинхүү; Д.Номин (Geological Issues, 2023)
This paper has been had about of engineering-geological sector in Mongolia, engineering-geological condition in Mongolia, plan for area city Ulaanbaatar, engineering-geological, study on determine soil standard index and policy engineering- geological and geotechnical of Ministry of construction and urban development.